Development of a Learning Module Using Constructive Alignment Theory in Project Managerial Course - Indriati, Lisa; Anggrianto, Christian (Bina Nusantara University, 2021)
The research intended to develop an ideal learning module using constructive alignment theory on Project Managerial course. It seemed difficult to draw firm conclusions about constructivism due to the various interpretations both pedagogically and epistemically. The mixed-method was used to survey 56 students participating in the Project Managerial course. Moreover, qualitative methods were implemented for deeper analysis. The methods provided an overview of the students’ level of understanding of the material, what they can do at the end of the lesson, as well as learning activities that can help students be actively involved in class. It was also to find out whether students have achieved the expected outcomes. The results prove that students’ understanding of the Project Managerial course is good, with an average score of 59,80 before the test and 85,88 after the test (n = 56). Students’ feedback shows that group assignment remains lacking of students’ participation with an average value of 3,4. In every relationship between the client and the designer, there are more or less the same systematic phases so that the results can be consistent. Different designers may have different terms. The research provides a big picture of the ideal design project management pattern. Whatever term is used later, of course, every successful design project must be managed properly and consistently.